The emergence of word-meaning in early China normative models for words - Geaney, Jane (SUNY series in Chinese philosophy and culture., 2022)
"Posits the origin of a specifically Chinese concept of "word-meaning," and sheds new light on the linguistic ideas in early Chinese philosophical texts"--